HUBUNGAN ANTARA PROGRAM GERAKAN LITERASI SEKOLAH DENGAN MINAT BACA SISWA - Jannah, Raudlatul (INCARE, International Journal of Educational Resources, 2021)
Low interest in reading is a problem in achieving students' language skills, including reading skills which have many benefits in students' language development. Therefore, the Ministry of Education and Culture created the School Literacy Movement (GLS) which is one step in instilling and growing student interest in reading. This study aims to analyze whether there is a relationship between the school literacy movement program and reading interest. The results of this study conclude that the school literacy movement has a significant positive relationship with students' reading interest. This is indicated by a significance value of 0.000 <0.05. The results of a simple correlation show a value of 0.628 so it can also be said that the better the school literacy movement, the higher the students' reading interest. The impact of this research is that the school literacy movement activity program can be an alternative to develop students' reading interest by providing reading material that is in accordance with their choices and interests through cultivating the school literacy ecosystem so that they become lifelong learners. Keyword : School Literacy Movement, Reading Interest